2022
DOI: 10.1007/s13280-022-01755-7
|View full text |Cite
|
Sign up to set email alerts
|

Cultural ecosystem services in European grasslands: A systematic review of threats

Abstract: The degradation of ecosystems threatens the provision of ecosystem services and limits human well-being. This systematic literature review evaluates the threats surrounding cultural ecosystem services (CES), namely recreation and landscape aesthetics in European permanent grasslands. We identified underlying causes, direct threats, consequences and suggested solutions for threat mitigation. The most common threats were land-use and management change processes, followed by social attitude, industrial developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 86 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…We see a need for monitoring the effect of innovations and new business models which may compromise some ecosystem services provided by grasslands. In addition, we recommend that the socio-economic and institutional readiness of business environments be included in the assessment to ensure the promotion of rural communities, communication with relevant stakeholders and sustainable development [7]. In doing so, sustainability research must address the specifics of each case to avoid continuing the path of blueprint solutions [102].…”
Section: Limits and Future Research Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We see a need for monitoring the effect of innovations and new business models which may compromise some ecosystem services provided by grasslands. In addition, we recommend that the socio-economic and institutional readiness of business environments be included in the assessment to ensure the promotion of rural communities, communication with relevant stakeholders and sustainable development [7]. In doing so, sustainability research must address the specifics of each case to avoid continuing the path of blueprint solutions [102].…”
Section: Limits and Future Research Topicsmentioning
confidence: 99%
“…In the EU, approximately 17.5% of the surface area is covered by grasslands and green shrubs [5]. Grasslands not only provide food and income for herders, but also provide essential ecological services such as climate regulation, wind prevention, biodiversity conservation and carbon fixation [6] as well as cultural services such as aesthetics and recreation [7]. A large fraction of this area has traditionally been utilized as pasture for livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Previous CES studies, on the other hand, found that dog walking and picnics are major recreation ecosystem service indicators that influence CES assessment patterns [36]. Picnic and camping areas are also seen as important features in the cultural landscape and green space management by several scholars [32,37,38]. In order to improve RES values for the majority of urban parks, it is therefore beneficial to reconsider urban park management regulations in order to suit the ever-changing aspirations of Beijing residents as the post-COVID-19 era continues.…”
Section: The Spatial Pattern Of Public Perceived Res Valuementioning
confidence: 99%
“…Several existing CES evaluation studies also demonstrate similar results. For instance, scholars [37,39,40] documented the significant contribution of grasslands and forestry lands towards RES value. In addition, previous research [1,8,40] identified water bodies as an important land cover that correlates to better recreation values and enhanced leisure possibilities.…”
Section: Impact Factors Towards Public-perceived Res Valuementioning
confidence: 99%
“…Some researchers argue that pleasure derived from the ecological functions of landscapes can increase aesthetic preferences [14,18]. At the same time, others argue that political, cultural, philosophical and ethical ideals influence how people are drawn to and prefer forest aesthetics [19,20]. While aesthetic quality is a crucial indicator and measure of urban green areas such as urban forests, the question of how to assess aesthetics persists [1,21].…”
Section: Introductionmentioning
confidence: 99%